2006
DOI: 10.1080/09537100600565551
|View full text |Cite
|
Sign up to set email alerts
|

Platelet inhibitory activity and pharmacokinetics of prasugrel (CS-747) a novel thienopyridine P2Y12 inhibitor: A single ascending dose study in healthy humans

Abstract: We assessed the tolerability, pharmacodynamics as measured by inhibition of platelet aggregation (IPA), and pharmacokinetics of prasugrel (CS-747, LY640315), a novel thienopyridine antiplatelet agent in healthy volunteers. Twenty-four subjects were randomized into four groups of six in a double-blind, placebo-controlled trial. One subject in each group received placebo and five subjects received prasugrel orally at single doses of 2.5, 10, 30, or 75 mg. The IPA, assessed using 5 and 20 microM ADP, was periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 22 publications
6
73
0
7
Order By: Relevance
“…The results for prasugrel are in agreement with previous studies of prasugrel [20,21] in healthy volunteers, but which did not include a clopidogrel comparison. Inhibition of platelet aggregation was greater with 10 and 20 mg prasugrel compared with clopidogrel 75 mg and the consistency of response to prasugrel was better than that observed with clopidogrel.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The results for prasugrel are in agreement with previous studies of prasugrel [20,21] in healthy volunteers, but which did not include a clopidogrel comparison. Inhibition of platelet aggregation was greater with 10 and 20 mg prasugrel compared with clopidogrel 75 mg and the consistency of response to prasugrel was better than that observed with clopidogrel.…”
Section: Discussionsupporting
confidence: 89%
“…In total, 10 doses were given to each subject. Previous single and 10-day multiple oral dose studies [20,21] in healthy subjects have shown that prasugrel 10 mg daily was well tolerated and produced a measurable and sustained pharmacodynamic effect on inhibition of platelet aggregation. Clopidogrel 75 mg is the approved clinical dose for maintenance therapy.…”
Section: Treatment Administeredmentioning
confidence: 97%
See 2 more Smart Citations
“…The pharmacokinetic properties of prasugrel and clopidogrel have been investigated in several studies and are summarized in Table 2. 12,[29][30][31][32][33][34][35][36][37][38][39][40][41][42] In contrast to clopidogrel, [43][44][45] genetic variants in CYP 2C19 genes have not been shown to affect the antiplatelet response to prasugrel. …”
Section: Current Recommendations For Thienopyridines As Add-on Antiplmentioning
confidence: 99%